Evaluation of the Baladi indirect tensile apparatus - Adam, John F.; United States. Federal Highway Administration; Iowa. Highway Division. Office of Materials (Ames, Iowa : Iowa Department of Transportation, Highway Division, 1990)
Evaluation of the effectiveness of a "device intended for reliable determination of asphalt concrete mechanical properties such as Poisson's ratio, resilient modulus, and indirect tensile strength"--P. 1.
Depository.
"January 1990."
"Final report for Iowa DOT project MLR-89-8."
"Federal Highway Administration Project DTFH71-89-511-IA-28."
Mode of access: Internet.
Keywords: Asphalt concrete -- Testing; CGP DTFH71-89-511-IA-28; CGP Iowa DOT project MLR-89-8.